2005
DOI: 10.2741/1705
|View full text |Cite
|
Sign up to set email alerts
|

The NA/K-ATPase and its isozymes: what we have learned using the baculovirus expression system

Abstract: The use of the baculovirus expression system for heterologous protein expression in insect cells has been of immense value in understanding many different structural and functional aspects of the Na/K-ATPase, an enzyme that catalyses the active exchange of cytoplasmic Na+ for extracellular K+ across the plasma membrane of most cells. The advantage of using insect cells is that they provide an eukaryotic expression system able to produce large amounts of active recombinant Na/K-ATPase for biochemical studies. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 141 publications
(183 reference statements)
1
31
0
1
Order By: Relevance
“…The large intracellular region of the Na,K-ATPase between transmembrane domains 4 and 5 has been shown to interact with the C-terminus of polycystin 1 (40,41). It is interesting that we found that, in insect cells, exogenous expression of a construct that contains the transmembrane and C-terminal domains of polycystin 1 increases the sensitivity of the Na,K-ATPase to ouabain, with the enzyme exhibiting a K i for the steroid that is similar to that found in ADPKD cells (42). Therefore, Na,K-ATPase-protein interaction represents another potential mechanism that is involved in the response of the cells to ouabain.…”
Section: Discussionsupporting
confidence: 48%
“…The large intracellular region of the Na,K-ATPase between transmembrane domains 4 and 5 has been shown to interact with the C-terminus of polycystin 1 (40,41). It is interesting that we found that, in insect cells, exogenous expression of a construct that contains the transmembrane and C-terminal domains of polycystin 1 increases the sensitivity of the Na,K-ATPase to ouabain, with the enzyme exhibiting a K i for the steroid that is similar to that found in ADPKD cells (42). Therefore, Na,K-ATPase-protein interaction represents another potential mechanism that is involved in the response of the cells to ouabain.…”
Section: Discussionsupporting
confidence: 48%
“…To date, four a-and b-subunit isoforms have been identified in mammals, which are expressed in a tissue-specific manner (17). A g-subunit can provide further tissue-specific regulation (18,19).…”
Section: Regulation Of the Nak-atpasementioning
confidence: 99%
“…It has been proposed that the Na,K-ATPase has other evolutionarily conserved physiological functions beyond ion transport. Particularly interesting is the requirement of the Na,K-ATPase in the formation and maintenance of intercellular junctions, where it can act as a signaling and scaffolding center (16)(17)(18).…”
Section: Regulation Of the Nak-atpasementioning
confidence: 99%
“…This problem can be circumvented by using heterologous expression systems. In the past, we have successfully used the baculovirus expression system to study different aspects of the enzymatic and regulatory properties of the Na-K-ATPase isoforms in insect cells (4). Sf-9 insect cells provide several advantages for the study of the Na-K-ATPase, including the production of high amounts of the ␣-and ␤-subunits and the proper delivery of catalytically competent Na-K-ATPase isozymes to the plasma membrane (4).…”
mentioning
confidence: 99%